Servo motors and industrial control theory - Firoozian, Riazollah (Mechanical Engineering Series, 2014)
Servo Motors and Industrial Control Theory is the only text focused on the fundamentals of servo motors and control theory. Graphical methods for classical control theory have been augmented with worked examples using MatLab and Mathcad to reflect the reality of the way engineers solve control problems in the field today. State variable feedback control theory is introduced clearly and simply, with practical examples that help students approach what can be seen as complicated problems with confidence. This updated second edition includes expanded discussion of Nyquist and Root Locus stability criteria and the role of sensors, as well as new Mathcad examples. A range of parameters are introduced for each servo control system discussed, making this book a comprehensive learning tool for students and an accessible information resource for control system designers who want to keep their knowledge up-to-date.